La sorpresa en la experiencia estética de la música popular - Cercado, Antonio (2024)
Popular music has used new technologies and the globalizing nature of our time to expand into different species of daily life. We live overstimulated by different rhythms, melodies and sounds. In this diverse context, how do we explain that we like something new? In what follows, we propose to explain the genesis of taste, starting from the temporal structure of surprise proposed by Natalie Depraz: anticipation-impression-resonance. The idea is to understand taste as a possibility of surprise; as a resonance of the first sound experience. In this way, a different perspective on the aesthetics of taste can be offered: outside or differentiating itself from established aesthetic models. Furthermore, it will be possible to understand how surprise participates in the origin of the different musical communities that are responsible for sustaining mass musical productions.